Dividend Dynamics and the Term Structure of Dividend Strips - BELO, FREDERICO; COLLIN‐DUFRESNE, PIERRE; GOLDSTEIN, ROBERT S. (Journal of Finance, 2015)
ABSTRACT Many leading asset pricing models are specified so that the term structure of dividend volatility is either flat or upward sloping. These models predict that the term structures of expected returns and volatilities on dividend strips (i.e., claims to dividends paid over a prespecified interval) are also upward sloping. However, the empirical evidence suggests otherwise. This discrepancy can be reconciled if these models replace their proposed dividend dynamics with processes that generate stationary leverage ratios. Under such policies, shareholders are forced to divest (invest) when leverage is low (high), which shifts risk from long‐ to short‐horizon dividend strips.